The current state of forensic psychiatric examination and provision of psychiatric help to persons with dependence status of psychoactive substances that have committed criminal offenses - Oliinyk, Оксана; Revenok, Олександр (Psychosomatic Medicine and General Practice, 2019)
Background. The steady increase in prevalence of mental disorders resulting from various dependence forms and high criminogenicity of such disorders led to a number of legislative changes in the field of jurisprudence, medicine and expertise. This problem became particularly relevant after the ratification of the agreement on the association of Ukraine with the European Union. European partners drew attention to the ineffectiveness of crime prevention measures committed by persons with addictions. Obtaining a visa-free regime between the EU and Ukraine has made it obligatory for the latter to take effective measures to solve this problem. Objective. To analyze and scientifically substantiate the relevance of legislative changes in forensic psychiatric examination and provision of psychiatric care to people with psychoactive substances dependence status who committed criminal offenses. Materials. For the scientific substantiation results of the forensic psychiatric examination of 368 sub-experts with the dependence on SAR were used. The sample was presented by a group with alcohol and narcotic addiction, 156 and 212 cases respectively. Analytical, clinical-anamnestic, clinical-psychopathological, statistical methods and the method of forensic psychiatric analysis were used for analysis and data processing. Results of researches indicate a high proportion of drug addicts in penitentiary institutions due to the low threshold for their prosecution. This demonstrates the ineffectiveness of harsh criminal approaches to people who are dependent and points to the need to humanize the state policy towards them. Conclusions. Legislation of Ukraine needs urgent changes in the issues of introducing alternative punishment for treatment of people with dependence status, formation of a network of specialized medical and rehabilitation centers, implementation of differentiated expert approaches in choosing medical measures of compulsory or alternative character. Forensic psychiatric examination is the first stage of the practical implementation of the declared legislative changes. Given current realities, experts themselves need social guarantees of their professional independence.